The influence of predominantly rural areas on the development path of Central and East-European regions with structural similarity - Anca Dachin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The real convergence process within the European Union at regional level is the main goal of the cohesion policy. Less developed regions belong mainly to Central and East European countries and aim at catching-up with other EU regions. According to Eurostat, Romania has 28 predominantly rural NUTS3 areas out of 42, situation that is usually associated with economic lagging behind. The paper focuses on the analysis of seven NUTS2 regions in Romania (excluding Bucharest-Ilfov) compared to other EU regions with structural similarity belonging to Bulgaria, Poland, Hungary, Czech Republic, Slovakia and Slovenia. All these regions have improved their GDP/capita in the period 2007- 2017, but most of them still have about 30-50% of the EU28 average. The purpose of the paper is to determine, by using the descriptive statistical analysis, to what extent the predominantly rural regions contributed to the slow rate of economic development at NUTS2 level in the last decade
Keywords: O18; R11; R23; 330; regional convergence; predominantly rural regions; structural similarity; economic development